Normalizing the illegal: public perceptions of vote-buying in West Bandung Regency and its democratic consequences - Djuyandi, Yusa; Nugraha, Kiki Pratama; Sugiharto, Agus; Jamri, Mohamad Hafifi; Ridzuan, Abdul Rauf (Frontiers in Political Science, 2025)
Generally, illegal activities are taboo to discuss, let alone perform. But does vote-buying carry the same stigma, or is it instead normalized as part of election tradition? This research investigates how the public perceives vote-buying practices and its impact on democracy, using a case study of West Bandung Regency, Indonesia. A quantitative survey was conducted on 1,200 respondents from November 10th to 14th, 2024, approximately 2 weeks before the 2024 Regional Elections (Pilkada). The findings reveal that vote-buying, despite its illegality, is not heavily stigmatized in the public eye. Nearly half of the respondents rationalized the practice in elections, and almost all of these respondents expressed willingness to accept money from candidates. Interestingly, a majority of those willing to accept money still stated they would vote according to their conscience—not the will of the vote “buyer”—in the secrecy of the polling booth. Furthermore, respondents tended to be responsive to the amount of money offered: the larger the sum, the more likely they were to comply with the payer's wishes—vice versa. These findings make a significant theoretical contribution by demonstrating that vote-buying, while widely considered wrong both legally and morally, nonetheless enjoys a high level of social acceptance. However, they contrast with traditional reciprocity theory, which assumes vote-buying functions like a transaction for goods/services; here, money does not always translate directly into votes, as voters still wish to vote according to their conscience. Practically, this research urges policymakers to address vote-buying systemically. It also criticizes previous solutions proven ineffective and suggests potential best solutions.